Variáveis determinantes do nível de divulgação de informações voluntárias ambientais - Giacomin, Juciléia (Universidade do Vale do Rio dos Sinos, 2016)
This study aimed to analyse the determinants of voluntary disclosure of environmental character information, a sample of forty-seven public companies listed on the BM & FBovespa and classified as high environmental impact, evidenced in Sustainability Reports and Management Report corresponding to fiscal year 2013. The research is applied as to its nature; quantitatively and the approach to the problem; descriptive and explanatory as to their purpose and documentary about the technical procedure used. In the first part of the analysis it is presented a descriptive analysis of data disclosed by companies, and in the second part, considering the results of previous studies and contributions from experts, eleven variables were tested and considered as possible determinants of this disclosure, through the use of multiple linear regression analysis. The level of environmental voluntary disclosure was measured by a metric containing eight categories and thirty-eight subcategories, suggested in a study conducted by Rover (2009). The main results of the study indicate that most disclosures were of the declarative type and categories more evidenced by the companies referred to the impact of products and processes and environmental policies. Size of the company, environmental certification and controlling interest were confirmed as determinants of the environmental voluntary disclosure level of the sample companies.
Keywords: Sustentabilidade; Fatores determinantes; Nível de divulgação voluntária; Sustainability; Determining factors; Voluntary disclosure level; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis